Translation Procedures in Translating Proper Names from English into Indonesian - Lestari, Ni Putu Devi; Winaya, I Made; Sosiowati, I Gst. Ayu Gede (Humanis; Vol 24 No 4 (2020), 2020)
Translation procedure is a procedure or a method to translate the unit of language from the source language to the target language. Every linguistic part needs to be translated. It means including the proper names in the literary work. This study is aimed at identifying and analyzing the types of the proper name and their translation procedures in the novel entitled Pembunuhan di Orient Express. The problems in this study are discussed based on the theory of proper name and the theory of the translation procedure by Newmark (1988). The method used to collect the data was documentation method. This study applied the descriptive qualitative method in analyzing the data. The result of the analysis was presented using an informal method. The analysis showed three types of proper names in the data sources. They are people’s names,   the name of an object, and the geographical term. The translator uses seven methods from 18 translation procedures that were proposed by Newmark (1988).